2022
DOI: 10.3389/fncel.2022.817752
|View full text |Cite
|
Sign up to set email alerts
|

Cellular and Molecular Gradients in the Ventral Horns With Increasing Distance From the Injury Site After Spinal Cord Contusion

Abstract: To identify cellular and molecular gradients following spinal cord injury (SCI), a rat contusion model of severe SCI was used to investigate the expression of NG2 and molecules that identify astrocytes and axons of the ventral horns (VH) at different distances on 7 and 30 days post-injury (dpi). A gradient of expression of NG2+/Olig2+ cells was determined, with the highest concentrations focused close to the injury site. A decrease in NG2 mean intensity correlates with a decrease in the number of NG2+ cells mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 50 publications
1
5
0
Order By: Relevance
“…Paradoxically, astrocyte perisynaptic processes marker GLT-1 was only increased in expression in 2-3 segments adjacent to the epicenter, which was measured both at 7 and 30 dpi. At 30 dpi, the square occupied by synaptophysin spots on the MNs perikarya and dendritic spines decreased [123]. These data indicate that, at least in the caudal direction, the synaptic loss is observed both near and at the already mentioned above greater distance from the area of damage.…”
Section: Perilesional Zone -Adjacent Segmentssupporting
confidence: 56%
See 3 more Smart Citations
“…Paradoxically, astrocyte perisynaptic processes marker GLT-1 was only increased in expression in 2-3 segments adjacent to the epicenter, which was measured both at 7 and 30 dpi. At 30 dpi, the square occupied by synaptophysin spots on the MNs perikarya and dendritic spines decreased [123]. These data indicate that, at least in the caudal direction, the synaptic loss is observed both near and at the already mentioned above greater distance from the area of damage.…”
Section: Perilesional Zone -Adjacent Segmentssupporting
confidence: 56%
“…Astrocytes near the injury site are actively involved in the remodeling of the extracellular matrix and synthesis of CSPGs that specifically inhibit axonal growth. Analysis of the astrocyte marker GFAP showed increased expression in adjacent segments, spreading more distally from the injury site [122,123]. These data indicate that the inhibitory effect of these molecules on axon growth manifests not only in the well-known immediate vicinity of the injury epicenter, but also at a distance from it.…”
Section: Perilesional Zone -Adjacent Segmentsmentioning
confidence: 69%
See 2 more Smart Citations
“…10E, F). A recent study also confirmed ◂ the diffusion of the wound response to adjacent and remote areas [123]. Conventional wisdom holds that secondary injury following SCI can be temporally divided into acute, sub-acute, and chronic phases [1,3,10,13,20,65].…”
Section: The Scar Boundary Is Interpreted By Stmentioning
confidence: 76%